A new method for skin grafting in murine model. Issue 4 (14th June 2016) - Pakyari, Mohammadreza; Farokhi, Ali; Khosravi‐Maharlooei, Mohsen; Kilani, Ruhangiz T.; Ghahary, Aziz; Brown, Erin
Abstract: Skin transplantation provides an excellent potential model to investigate the immunology of allograft rejection and tolerance induction. Despite the theoretical ease of performing skin transplantation, as well as the potential of directly observing the reaction to the transplanted tissue, the poor reliability of skin transplantation in the mouse has largely precluded the use of this model. Furthermore, there is controversy regarding the most appropriate skin graft donor site due to poor success of back skin transplantation, as compared with the thinner ear or tail skin. This study demonstrates a reliable method to successfully perform skin grafts in a mouse model, as well as the clinical and histologic outcome of syngeneic grafts. A total of 287 grafts were performed (in 126 mice) utilizing donor skin from the ear, tail or back. No graft failure or postoperative mortality was observed. Comparison of this technique with two previously established protocols of skin transplantation (5.0 absorbable Suture + tissue glue technique and no‐suture technique) demonstrates the significant improvement in the engraftment success of the new technique. In summary, a new technique for murine skin grafting demonstrates improved reliability across donor site locations and strains, increasing the potential for investigating interventions to alter the rejection process.